Design and construction of a solar tracking system for small-scale linear Fresnel reflector with three movements. (1st March 2021) - Barbón, A.; Fernández-Rubiera, J.A.; Martínez-Valledor, L.; Pérez-Fernández, A.; Bayón, L.
Abstract: A new open-loop solar tracking system for a small-scale linear Fresnel reflector with three movements has been designed, fabricated, and simulated. The control system of the solar tracker is governed by a Raspberry Pi together with other auxiliary devices which include a Global Positioning System. The electronic control system consists of a master controller (Raspberry pi 3), 4 slave microcontrollers (Arduino), Global Positioning System module, thermocouples, laser sensors, transversal positioning sensors, and longitudinal positioning sensors. It also allows the communication between these microcontrollers based on long range wireless solutions (XBee). All the electronic circuits have been designed and constructed. The solar tracking system uses offline data. The software has been designed and developed to track the sun path using astronomical equations. In this way, the solar tracking system is able to position itself automatically using the solar position algorithm and the Global Positioning System with an accuracy of ±0.006°. The solar tracking system can be deployed automatically at any location on the Earth. The total cost of the implemented solar tracking system has been calculated. The system performance, in terms of the tracking error, annual energy, energy-to-area ratio and levelized cost of energy has been evaluated. Tracking errors smaller than 0.06 (°) are acceptable (they cause power losses smaller than 1%), whereas errors larger than 0.36 (°) start being noticeable (power losses greater than 3%). The proposed new tracking system gives 16.64% more energy, a 78.46% higher energy-to-area ratio, and a 4.62% less levelized cost of energy that the classic tracking system with one movement used in large-scale linear Fresnel reflectors. Highlights: A new tracking system for a Fresnel reflector has been designed and simulated. We designed and constructed all electronic circuits and we calculated its cost. We have compared the absorbed power in two cases: with and without tracking errors. The new system gives 16.64% more energy than the classic tracking systems. And it also gives a 78.46% higher energy-to-area ratio than the classic systems.